Lobar versus sublobar resection in clinical stage IA primary lung cancer with occult N2 disease. (5th September 2022) - Liou, Douglas Z; Chan, Michelle; Bhandari, Prasha; Lui, Natalie S; Backhus, Leah M; Shrager, Joseph B; Berry, Mark F
Abstract: OBJECTIVES: Sublobar resection is increasingly being utilized for early-stage lung cancers, but optimal management when final pathology shows unsuspected mediastinal nodal disease is unclear. This study tested the hypothesis that lobectomy has improved survival compared to sublobar resection for clinical stage IA tumours with occult N2 disease. METHODS: The use of sublobar resection and lobectomy for patients in the National Cancer Database who underwent primary surgical resection for clinical stage IA non-small-cell lung cancer with pathologic N2 disease between 2010 and 2017 was evaluated using logistic regression. Survival was assessed with Kaplan–Meier analysis, log-rank test and Cox proportional hazards model. RESULTS: A total of 2419 patients comprised the study cohort, including 320 sublobar resections (13.2%) and 2099 lobectomies (86.8%). Older age, female sex, smaller tumour size and treatment at an academic facility predicted the use of sublobar resection. Patients undergoing lobectomy had larger tumours (2.40 vs 2.05 cm, P  < 0.001) and more lymph nodes examined (11 vs 5, P  < 0.001). Adjuvant chemotherapy use was similar between the 2 groups (sublobar 79.4% vs lobectomy 77.4%, P  = 0.434). Sublobar resection was not associated with worse survival compared to lobectomy in both univariate (5-year survival 46.6% vs 45.2%, P  = 0.319) and multivariable Cox proportional hazards analysis (hazard ratio 0.97, P  = 0.789). CONCLUSIONS: Clinical stage IA non-small-cell lung cancer patients with N2 disease on final pathology have similar long-term survival with either sublobar resection or lobectomy. Patients with occult N2 disease after sublobar resection may not require reoperation for completion lobectomy but should instead proceed to adjuvant chemotherapy. Abstract : Lung cancer accounts for nearly a quarter of all cancer-related deaths in the USA, with around 80% of cases diagnosed as non-small-cell lung cancer (NSCLC) [1].